PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN BANTUAN MEDIA KARTU DOMINO UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS XI MIA 2 SMAN 1 LANGGAM TAHUN PELAJARAN 2019/2020 - Mutia Irfina Muslima Almi; Arnentis Arnentis; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aimed to improve Student’achievement of students in class XI MIA 2 of SMA Negeri 1 Langgam by implementation of Cooperative Learning Model STAD is assited by domino card It was done in SMA Negeri 1 Langgam on Agustus of September 2019. Parameters which measure were student’s achievement. The methods of this research was classroom action research by implementation of Cooperative Learning Model STAD is assited by domino card. It was done in two cylce. There were planning step, acting step, observation step and reflection step for each cycle. The first cycle to apply learning materials about the structure and function of plant tissue and in the second cycle about the structure and function of animal tissue. The research instrument used was a learning device that consist of a lesson plan, syllabus, assesment authentic sheet, observation shee. The result of this research showed that Student’achievement in the first cycle was 80,87 with a enough categories and increased in the second cycle up to 87,95 with a good categories. Completeness percentage in the first cycle was 75% and increased in the second cycle up to 100%. Student’s attitude in the first cycle was 80,91 with a enough categories and increased in the second cycle up to 85,55 with a good categories. The value of students’ presentation skills in the first cycle was 80,53 with a enough categories and increased in the second cycle up to 84,94 with a predicate good categories. It can be conclude that application of the STAD type cooperative learning model with the help of domino card in biology subjects can improve can improve learning outcomes of student in class XI MIA 2 SMA Negeri 1 Langgam.Key Words: Cooperative Type STAD, Domino Card, Learning Outcomes